Women and their Body
Women’s rights over their own bodies is one of the most pressing issues, esp. as women still seem to have fewer rights over their bodies than men. International authors from philosophy, literature, art, architecture, and gender studies address the topic from a variety of perspectives, reaching beyond classical feminism, and beyond the labels of "motherhood" and "sex." The contributions are grouped into five sections – Body Experiences, History, Technology and Arts, Feminism and Phenomenology, and Beauty. Papers address a multitude of areas, ranging from beauty practices and Ukrainian women refugees in the context of the Russia-Ukraine war, feminist phenomenology and socio-structural critique, female specific neuropathology, the discourse of the Victorian women’s menstruation to "motherhood" in gender studies and feminist new materialisms. The book provides not only a comprehensive overview over the current state of research, but will also inspire further discussions. A separate bibliography listing relevant titles for readers new to the topics and for advanced researchers rounds out the volume.

Symplectic Lattices and GKP Codes -- Simple Randomized Constructions from Cryptographic Lattices - Blömer, Johannes; Xiao, Yinzi; Raissi, Zahra; Soltan, Stanislaw (arXiv:2509.10183)
We construct good GKP (Gottesman-Kitaev-Preskill) codes (in the sense of Conrad, Eisert and Seifert proposed) from standard short integer solution lattices (SIS) as well as from ring SIS and module SIS lattices, R-SIS and M-SIS lattices, respectively. These lattice are crucial for lattice-based cryptography. Our construction yields GKP codes with distance $\sqrt{n/πe}$. This compares favorably with the NTRU-based construction by Conrad et al. that achieves distance $Ω(\sqrt{n/q}),$ with $n\le q^2/0.28$. Unlike their codes, our codes do not have secret keys that can be used to speed-up the decoding. However, we present a simple decoding algorithm that, for many parameter choices, experimentally yields decoding results similar to the ones for NTRU-based codes. Using the R-SIS and M-SIS construction, our simple decoding algorithm runs in nearly linear time. Following Conrad, Eisert and Seifert's work, our construction of GKP codes follows directly from an explicit, randomized construction of symplectic lattices with (up to constants $≈ 1$) minimal distance $(1/σ_{2n})^{1/2n}≈ \sqrt{\frac{n}{πe}}$, where $σ_{2n}$ is the volume of the 2n-dimensional unit ball. Before this result, Buser and Sarnak gave a non-constructive proof for the existence of such symplectic lattices.

1 1Introduction Women and Their Body: Breaking the Silence - Muller, Jil (Women and Their Body)

Projektmanagement Und Vorgehensmodelle 2025 – Post-Agilität, Resilienz, Transformation - Linssen, Oliver; Volland, Alexander; Yigitbas, Enes; Engstler, Martin; Bertram, Martin; Hanser, Eckhart; Kalenborn, Axel

Non*binär! Sound und Gender im Posthumanismus
Wie klingt ein nonbinäres Subjekt? Band 17 des Jahrbuchs Musik und Gender entwickelt neue Perspektiven für die musikwissenschaftliche Genderforschung, indem er sie um posthumanistische Ansätze erweitert. Die Denkfigur der Nonbinarität bricht dabei nicht nur Geschlechtergrenzen auf, sondern auch die Grenzen zwischen Mensch und Nichtmensch, Natur und Technik. Die Autor:innen aus Wissenschaft und Kunst schaffen mit ihren Beiträgen ein komplexes Beziehungsnetzwerk, das neue Hörweisen ermöglicht, alte und neue Verbindungen schafft: Sonic Fiction trifft auf Trauerarbeit um verlorene Stimmen; frühe Gendertheorie auf Öko- und Queerfeminismus. Ein vielstimmiger Band, der – wichtiger denn je – neue Formen des Zuhörens erschließt.
Keywords: posthumanism; feminist theory; nonbinary; sound studies; musicology

“Extinction Is an Opportunity.” – The Transformative Potential of Post-Apocalyptic Video Game Spaces - Skuratova, Angelina (Data – Culture – Society. Kulturwissenschaftliche Perspektiven auf Data Society als gesellschaftliche Transformation)

Rezension zu: „The Bible in Folklore Worldwide. Volume 2: A Handbook of Biblical Reception in Folklores of Africa, Asia, Oceania, and the Americas“ - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Rezension zu: „Moses Quellwasserwunder. Ex 17 und Paraschat Chukkat (Num 20) in jüdischen und christlichen Bildrezeptionen” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik)

Rezension zu: „Heilige Sprache (JBTh 39)” - Bergmann, Claudia Dorit (Theologie der Gegenwart)

Electro-optic frequency shift of single photons from a quantum dot - Kapoor, Sanjay; Rodek, Aleksander; Mikołajczyk, Michał; Szuniewicz, Jerzy; Sośnicki, Filip Maksymilian; Kazimierczuk, Tomasz; Kossacki, Piotr; Karpiński, Michał (Nanophotonics)
Quantum dots (QDs) are a promising source of single photons mainly due to their on-demand operation. However, their emission wavelength depends on their size and immediate surroundings in the solid-state environment. By applying a serrodyne electro-optic phase modulation, we achieve a spectral shift up to 0.01 nm (3.5 GHz) while preserving the purity and indistinguishability of the photons. This method provides an efficient and scalable approach for tuning the emission wavelength of QDs without relying on nonlinear frequency mixing or probabilistic processes. Our results show that the electro-optic phase modulation enables stable and tunable spectral shifts, making it suitable for applications such as quantum communication, quantum key distribution, and primarily integrating remote quantum dot sources into large-scale quantum networks.

Aberration-optimized electro-optic time lens model using a tunable aperture - Kapoor, Sanjay; Sośnicki, Filip Maksymilian; Karpiński, Michał (APL Photonics)
Time lenses have been recognized as crucial components for manipulating ultrafast optical pulses in various applications, from ultrafast spectroscopy to the interfacing of optical quantum systems. A time lens is characterized by its chirp rate, which determines the focusing strength of the time lens, and accurate knowledge of this chirp is critical for precise dispersion compensation and minimizing aberrations. Here, we introduce a tunable time aperture model for sinusoidal time lenses that provides a more accurate estimate of the effective chirp rate without modifying the device. We derive a closed-form expression for the maximum phase error and show how it depends on the time aperture. We experimentally demonstrate a 1.6-fold improvement in spectral bandwidth compression of Gaussian pulses compared to the conventional approach. Our framework offers a practical tool for designing efficient temporal optical systems, benefiting applications in both classical and quantum optics where accurate spectro-temporal shaping is essential.

Frühe mathematische Bildung als Ausbildungsinhalt der Erzieherinnen- und Erzieher-Ausbildung stärken - Bruns, Julia; Gasteiger, Hedwig; Lastering, Bernd; Schopferer, Theresa; Zech, Detlev (25 Jahre Berufskolleg - Wegspuren und Zukunftspfade)

Advancing excited-state properties of two-dimensional materials using a dielectric-dependent hybrid functional - Ghosh, Arghya; Jana, Subrata; Hossain, Manoar; Rani, Dimple; Śmiga, Szymon; Samal, Prasanjit (Physical Review B)
Predicting accurate band gaps and optical properties of lower-dimensional materials, including two-dimensional van der Waals (vdW) materials and their heterostructures, remains a challenge within density functional theory (DFT) due to their unique screening compared to their bulk counterparts. Additionally, accurate treatment of the dielectric response is crucial for developing and applying screened-exchange dielectric-dependent range-separated hybrid functionals (SE-DD-RSH) for vdW materials. In this work, we introduce a SE-DD-RSH functional to the 2D vdW materials like <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"><a:msub><a:mi>MoS</a:mi><a:mn>2</a:mn></a:msub></a:math>, <b:math xmlns:b="http://www.w3.org/1998/Math/MathML"><b:msub><b:mi>WS</b:mi><b:mn>2</b:mn></b:msub></b:math>, <c:math xmlns:c="http://www.w3.org/1998/Math/MathML"><c:mrow><c:mi>h</c:mi><c:mi>BN</c:mi></c:mrow></c:math>, black phosphorus (BP), and <d:math xmlns:d="http://www.w3.org/1998/Math/MathML"><d:mi>β</d:mi><d:mtext>−</d:mtext><d:mi>InSe</d:mi></d:math>. By accounting for in-plane and out-of-plane dielectric responses, our method achieves accuracy comparable to advanced many-body techniques like <e:math xmlns:e="http://www.w3.org/1998/Math/MathML"><e:mrow><e:msub><e:mi>G</e:mi><e:mn>0</e:mn></e:msub><e:msub><e:mi>W</e:mi><e:mn>0</e:mn></e:msub></e:mrow></e:math> and BSE@<f:math xmlns:f="http://www.w3.org/1998/Math/MathML"><f:mrow><f:msub><f:mi>G</f:mi><f:mn>0</f:mn></f:msub><f:msub><f:mi>W</f:mi><f:mn>0</f:mn></f:msub></f:mrow></f:math> at a lower computational cost. We demonstrate improved band gap predictions and optical absorption spectra for both bulk and layered structures, including some heterostructures like <g:math xmlns:g="http://www.w3.org/1998/Math/MathML"><g:msub><g:mi>MoS</g:mi><g:mn>2</g:mn></g:msub><g:mo>/</g:mo><g:msub><g:mi>WS</g:mi><g:mn>2</g:mn></g:msub></g:math>. This approach offers a practical and precise tool for exploring electronic and optical phenomena in 2D materials, paving the way for efficient computational studies of layered systems.

Words or Numbers? How Framing Uncertainties Affects Risk Assessment and Decision-Making - Bodenberger, Robin; Thommes, Kirsten
Senders of messages prefer to communicate uncertainty verbally (e.g., something is likely to happen) rather than numerically (such as 75%), leaving receivers with imprecise information. While it is well established that receivers translate verbal probabilities into numerical values that systematically deviate from the intended numerical meaning, it is less clear how this discrepancy influences subsequent behavioral actions. Thus, the role of verbal versus numerical communication of uncertainty warrants additional attention, to investigate two critical questions: 1) whether differences in decision-making under uncertainty arise between these communication forms, and 2) whether such differences persist even when verbal phrases are translated accurately into the intended numerical meaning. By implementing a laboratory experiment, we show that individuals place significantly lower values on uncertain options with medium to high likelihoods when uncertainty is communicated verbally rather than numerically. This effect may lead to less rational decisions under verbal communication, particularly at high likelihoods. Those results remain consistent even if individuals translate verbal uncertainty correctly into the intended numerical uncertainty, implying that a biased behavioral response is not only induced by miscommunication. Instead, ambiguity about the exact meaning of a verbal phrase interferes with decision-making even beyond potential mistranslations. These findings tie in with previous research on ambiguity aversion, which has predominantly operationalized ambiguity through numerical ranges rather than verbal phrases. Based on our findings we conclude that managers should communicate uncertainty numerically, as verbal communication can unintentionally influence the decision-making process of employees.

Foreign Language Use, Attribution Error, and Newcomer Integration - Thommes, Kirsten; Mehic, Miro

Soziale Medien als algorithmische Diskursmaschinen - Herzig, Bardo (SLLD (B). Spachlich literatisches Lernen und Deutschdidaktik)

Query Rewriting for Nested Navigational Queries over Property Graphs - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (Proceedings of the 38th International Workshop on Description Logics (DL 2025), Opole, Poland, September 3-6, 2025.)

Ressourcenräume: Seerecht, Geopolitik und Wissenschaftsdiplomatie zwischen den Seychellen, Frankreich und der Bundesrepublik Deutschland um 1980 - Kunkel, Sönke; Sackel, Johanna (Räume in der Internationalen Geschichte)

Rechnen mit Beziehungen - operative Beziehungen erkennen, beschreiben und nutzen. Entwicklung einer digitalbasierten Lernumgebung mit der App Rechenfeld - Dettelbach, Andrea (Beiträge zum Mathematikunterricht 2025)

Normatives Modellieren im Kontext des Klimawandels – wie viel CO2 stoßen Lebensmittel aus? - Gildehaus, Lara; Liebendörfer, Michael; Hüsing, Sven; Gottschalk, Rebecca; Strauß, Franzisca (Realitätsbezüge im Mathematikunterricht)